Workplace Learning in Context - Fuller, Alison; Rainbird, Helen; Munro, Anne (USA, Canada Routledge, 2004)
As policy makers increasingly focus on workplace learning as a way of improving organizational performance, the debate about the learning organization has grown. Counterbalancing the often over-optimistic assumptions made about the future of work and learning, this book argues that without a contextualized analysis of the field, our understanding of the learning environment is limited. It reconsiders the true role and nature of workplace learning in context.
Age Group: Adult
Keywords: (ETB-2007) Travel and Tourism Work Placement